Oxidative low-density lipoprotein and shear induced calcification within a calcific aortic valve disease-on-a-chip platform - Mendoza-Seale, Melissa; Chen, Mei-Hsiu; Huang, Peter; Mahler, Gretchen J. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEarly-stage calcific aortic valve disease (CAVD) has been characterized by the infiltration of immune cells, reorganization of the extracellular matrix, and the deposition and oxidation of low-density lipoproteins (oxLDL). Worldwide studies have revealed that aortic valve disease accounts for up to 43% of patients exhibiting heart disease.MethodsWe utilized a CAVD-on-a-chip platform of the aortic valve fibrosa to assess the hypothesis that culture calcification will increase with endothelial cell presence, increased oxLDL concentration (25 μg/ml or 50 μg/ml), and shear stress (20 dyne/cm2). CAVD chips consisted of collagen I hydrogels with porcine aortic valve interstitial cells embedded and porcine aortic valve endothelial cells seeded on top of the matrix for up to two days.ResultsHere, we demonstrate that the presence of endothelial cells and shear stress drives alkaline phosphatase activity, sulfated glycosaminoglycan production, and the formation of mono-, di-, and octa- calcium phosphates, and hydroxyapatites. Two-day dynamic cultures showed 3D cell-oxLDL interactions, leading to extracellular matrix remodeling and endothelial dysfunction.DiscussionGiven that CAVD has no targeted intervention, continued evolution of this CAVD-on-a-chip model sheds light on mechanisms in disease onset and can lead to significant contributions in preclinical drug development.